Policy-Driven Research, Audit Culture and Power: Transforming Sociological Practices in the Philippines and Asia - Porio, Emma E (Archīum Ateneo, 2012)
During the last few decades, universities in the South have increasingly been pressured to engage in policy-relevant research and to produce knowledge that is useful for national development. Alongside this trend is the emergence of the audit/assessment culture and knowledge management systems among bi/multi-lateral institutions engaged in overseas development assistance (ODA) programs and in higher education as well. Thus, university ranking systems, which reflect the penetration of the audit culture in academia, have become central in the sets of policies and programs that institutions of higher learning have crafted to become more competitive nationally, regionally or globally.